2022
DOI: 10.1073/pnas.2203925119
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for adaptive morphological plasticity in the Caribbean coral, Acropora cervicornis

Abstract: Genotype-by-environment interactions (GxE) indicate that variation in organismal traits cannot be explained by fixed effects of genetics or site-specific plastic responses alone. For tropical coral reefs experiencing dramatic environmental change, identifying the contributions of genotype, environment, and GxE on coral performance will be vital for both predicting persistence and developing restoration strategies. We quantified the impacts of G, E, and GxE on the morphology and survival of the endangered coral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 120 publications
0
11
1
Order By: Relevance
“…While variation in growth, reproductive success, and stress tolerance across genotypes of A. cervicornis and A. palmata (Baums et al, 2013; Lohr & Patterson, 2017; Muller et al, 2021) demonstrate genetic constraints on coral fitness, phenotypic plasticity has also been reported in both species (Durante et al, 2019; Kuffner et al, 2017; Million et al, 2022). Indeed, A. cervicornis and A. palmata corals studied in the present work demonstrated environmentally induced plasticity, with environmental factors more strongly influencing the physiology of both species compared with the effect of coral genotype (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While variation in growth, reproductive success, and stress tolerance across genotypes of A. cervicornis and A. palmata (Baums et al, 2013; Lohr & Patterson, 2017; Muller et al, 2021) demonstrate genetic constraints on coral fitness, phenotypic plasticity has also been reported in both species (Durante et al, 2019; Kuffner et al, 2017; Million et al, 2022). Indeed, A. cervicornis and A. palmata corals studied in the present work demonstrated environmentally induced plasticity, with environmental factors more strongly influencing the physiology of both species compared with the effect of coral genotype (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The significant interactive effects of genotype × site and genotype × season observed to influence coral physiology in A. cervicornis (Table 2 and Table S5) corroborate recent reports of genotype by environment interactions (GxE) in the phenotype of this species. Reciprocal transplant experiments across the Florida Reef Tract found that GxE affected the growth, morphology, bleaching response and survival of A. cervicornis (Drury et al, 2017; Drury & Lirman, 2021; Million et al, 2022). In the present work, GxE influenced the biomass and protein of the host, as well as both chlorophyll‐a and ‐c2 in A. cervicornis (Table S5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These contrasting results may be due to different experimental design considerations across studies (Bove et al, 2020), especially given that the heat stress temperature employed here (~30.5 ˚C) was lower than most other warming studies. However, there is also significant genetic variation within A. cervicornis (Drury et al, 2017;Million et al, 2022), thus it is also possible that the genotypes used in this study were particularly resistant. Alternatively, these corals are already exposed to warmer seawater conditions where they were collected compared to other Caribbean reefs (Muñiz-Castillo et al, 2019;Bove et al, 2022b), suggesting the potential for acclimatization to elevated temperatures.…”
Section: Global Change Treatment Elicits Subtle Stress Signaturesmentioning
confidence: 99%